Islamophobia in the most populous Muslim majority country: a case study of Indonesia - Mohamad Shukri, Syaza Farhana (2018)
Islamophobia has been on the rise in the twenty-first century. Muslims from all over the world has been subjected to prejudice, hatred and fear based simply on their perceived religious affiliation. This is the new reality facing Muslims especially those living in the West, making it difficult for them to live a normal life. Scholars have debated this issue from the historical development of Islamophobia to the mistakes policymakers made in dealing with Islamophobia. It has been found that Islamophobia is the product of a systematic attack on Islam and Muslims by people who have an agenda to keep the world divided for their benefit. While this much we know, what is obviously missing in current literature is research from the perspective of non-western communities. Through the conduct of a focus group and thematic analysis of primary and secondary sources, this research aims to discover the causes of Islamophobia in Indonesia in the twenty-first century and its impact. With the rise of Islamic extremism, there has been a parallel rise in Islamophobia in Indonesia. Moreover, the study discovers that Islamophobic sentiment can be found not only among non-Muslims, but also among Muslims towards other Muslims. In combating Islamophobia, it is important for us to understand the new trend of rising conservatism in a country that prides itself with its own indigenous culture.